2017
DOI: 10.1111/jfpp.13320
|View full text |Cite
|
Sign up to set email alerts
|

Forced-air precooling treatment enhanced antioxidant capacities of apricots

Abstract: Effects of forced-air precooling on fruit quality and antioxidant system of apricot were evaluated in this study. Apricots were forced-air precooled for 24 hr at 08C, and then stored at 08C for up to 20 days. Results showed that precooling treatment slowed down a decrease of titratable acidity (TA) and total soluble solids (TSS) during storage period, whereas it had no effect on pH and L* value. On the 15th day of storage, associated with higher flavonoids content, precooled fruit had 73.6% higher DPPH and 183… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…e change of SSC, TA, and starch content might be related to the delay in the ripening process and reduction of respiration rate. In coincidence with the previous study on apricot [10], precooling treatment enhanced avonoids content in mango fruits in the late stage of storage. Flavonoids content is an important indicator of fruit's antioxidant capacity [32], and precooling treatment might contribute to mango fruits antioxidant capacities.…”
Section: Journal Of Food Qualitysupporting
confidence: 88%
See 1 more Smart Citation
“…e change of SSC, TA, and starch content might be related to the delay in the ripening process and reduction of respiration rate. In coincidence with the previous study on apricot [10], precooling treatment enhanced avonoids content in mango fruits in the late stage of storage. Flavonoids content is an important indicator of fruit's antioxidant capacity [32], and precooling treatment might contribute to mango fruits antioxidant capacities.…”
Section: Journal Of Food Qualitysupporting
confidence: 88%
“…Among various industrial postharvest precooling techniques, forced air precooling is widely accepted as an e ective method to maintain postharvest quality and prolong shelf-life for many fruits like apple and plum [7][8][9]. Forced air cooling is much faster than other conventional cooling methods because the cool air comes in direct contact with the surfaces of the horticultural product [10].…”
Section: Introductionmentioning
confidence: 99%
“…The result indicated that the volatile content was affected by many other factors. Besides genetic makeup, the differences in the volatile profile and fruit quality among the cultivars were dependent upon the environment, management, fertilizers, and harvest maturity [26,27,28,29].…”
Section: Resultsmentioning
confidence: 99%
“…The identification of volatile compounds was based on comparisons of RI and mass‐fragmented patterns with standards, with mass spectra in the NIST Database, and/or previously published studies. All quantifications were carried out in triplicate, and the experimental results are expressed as mean and standard deviations (Yan, Song, Li, & Jiang, ).…”
Section: Methodsmentioning
confidence: 99%